The way out of the wilderness learn how Bible heroes with feet of clay are models for your recovery - Henslin, Earl R. (Nashville, TN Thomas Nelson, 1991)
Includes bibliographical references.
Keywords: Adult children of dysfunctional families -- religious life; Codependants -- religious life; Shame -- religious aspects -- Christianity; Problem families -- biblical teaching; Families -- religious life